Oxidative stress associated with pathological lesions in the liver of rats experimentally infected by Fasciola hepatica - Bottari N.B. (2015)
© 2015 Elsevier Inc.The aim of this study was to analyze the antioxidant status and oxidative profile in serum and liver of rats experimentally infected with Fasciola hepatica and its relationship with pathological findings. Twenty-four rats were divided into two groups: group A consisted of 12 healthy rats and group B of 12 rats infected orally with 20 metacercaria of F. hepatica. At days 20 and 150 post-infection (PI), blood and liver samples of six animals from each group were collected. The protein oxidation (AOPP technique: advanced oxidation protein products) and antioxidants (FRAP technique: ferric reducing antioxidant power) levels were measured in serum and liver. Furthermore, nitrite/nitrate (NOx) levels and lipid peroxidation (TBARS technique: thiobarbituric acid reactive substances) were measured in liver. AOPP and FRAP levels were increased (P < 0.05) in serum and liver of infected animals in acute and chronic infection when compared with healthy animals. The same occurred with TBARS and NOx levels in the liver (P < 0.05). Histopathology revealed periportal fibrous hepatitis, composed of an abundant inflammatory infiltrate in portal spaces on infected animals, as well as bile duct hyperplasia. The results found seem to be related to the host free radical production demonstrated in serum samples and liver due to the parasite infection.